The Effectiveness of Digital Collaboration through Interactive Flat Panel Displays in Stimulating Early Numeracy Skills - Santi Trisniawati; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to explore the effectiveness of digital collaboration through Interactive Flat Panel Displays (IFPD) in stimulating young children’s early numeracy skills at TK Aisyiyah Ngunut, as well as the factors influencing its implementation. The study employed a qualitative case study approach, with data collected through semi-structured interviews with the principal, early childhood education teachers, and parents, as well as participatory classroom observations. The findings indicate that the use of IFPD increased children’s engagement, motivation, independence, and numeracy skills. Children were able to understand number concepts, grouping, simple addition, and number sequences through direct interaction with digital media. Collaborative activities also strengthened children’s social skills and teamwork. The successful implementation of IFPD was influenced by teacher competence, the quality of digital content, parental support, and device readiness. These findings suggest that IFPD is an interactive and effective learning medium for stimulating early childhood numeracy skills when supported by adequate enabling factors.